Interferences of Bandung Creative City in Developing the Creative Economy of Bandung City - Mohamad Ichsana Nur; Roy Valiant Salomo; Khaerul Umam; Siti Alia (Iapa Proceedings Conference, 2019)
This present research aims to analyze the interferences of the Bandung Creative City Forum (BCCF) as a representative of creative economy communities in the development of creative economy in the City of Bandung. This research is descriptive research with post-positivist approach and used in-depth interviews as well as document studies as the data collection methods. The results show that the BCCF as an independent societal organization concerned with the development of creative economy in the City of Bandung was able to run a number of internal and external activities effectively and made physical and social contributions directly felt by citizens and the city. However, the BCCF is faced with the reality that in the meantime, they are utterly different from they were in the forgoing two periods. For this reason, the BCCF is striving to adapt with their needs in the present time while keeping on carrying out their previous positive activities, especially those directly linked with the citizens of the City of Bandung.